Advanced Dressing Therapy of Diabetic Foot Ulcers in Wound Care Clinic Prevents Limb Amputation: A Case Report Study - Hazazi, Ahmed Abutaleb; Sahli, Shaqra Saleh; Medkhali, Abdulgabar Gaber; Sumayli, Waleed Mohammed; Majrashi, Abdulaziz Ahmed; Ibrahim, Majed Mohammed Hadi; Sahly, Ali Ibrahim Yahya; Ageeli, Wael Mohammed; Afandi, Rawan Abdulrahman; Dagriry, Maryam Husain (Journal of Ecohumanism, 2024)
The global prevalence of type 2 diabetes mellitus (T2DM) continues to rise significantly, with particularly concerning rates in Saudi Arabia. This increase has led to a proportional rise in diabetes-related complications, with diabetic foot ulcers (DFUs) representing one of the most challenging and potentially devastating consequences. This case report presents the successful implementation of advanced dressing therapy to prevent lower limb amputation in a patient with complex DFUs in a specialized wound care clinic. We document the case of a 65-year-old male with a 30-year history of T2DM who presented to the Emergency Department with a septic foot and peripheral vasculopathy complicated by a chronic wound. Following the patient's refusal of amputation, specialized wound care nurses implemented a comprehensive treatment protocol incorporating multiple advanced dressing techniques, including antibacterial solutions, autolytic debridement gels, charcoal-silver dressings, and protective absorption foam. The treatment strategy was systematically adjusted according to wound healing stages over six months of careful monitoring. The initial wound, measuring 8×10 cm with purulent discharge and necrotic tissue, showed remarkable improvement, with healthy granulation tissue emerging within three weeks of treatment initiation. Through the strategic use of advanced dressing products for wound bed preparation and matrix therapy with heparin sulfate solution during the maturation phase, complete wound healing was achieved with minimal scarring. This case demonstrates the potential of specialized wound care protocols in preventing amputation and achieving optimal healing outcomes in complex DFUs while highlighting the crucial role of dedicated wound care nurses in delivering comprehensive care.